2013
DOI: 10.1088/0004-637x/766/2/97
|View full text |Cite
|
Sign up to set email alerts
|

The Fragmentation of Magnetized, Massive Star-Forming Cores With Radiative Feedback

Abstract: We present a set of 3-dimensional, radiation-magnetohydrodynamic calculations of the gravitational collapse of massive (300 M ), star-forming molecular cloud cores. We show that the combined effects of magnetic fields and radiative feedback strongly suppress core fragmentation, leading to the production of single star systems rather than small clusters. We find that the two processes are efficient at suppressing fragmentation in different regimes, with the feedback most effective in the dense, central region a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
251
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 186 publications
(269 citation statements)
references
References 81 publications
17
251
1
Order By: Relevance
“…Indeed, we note that the relative unimportance of magnetic fields as opposed to radiation in preventing fragmentation on small scales around stars, as opposed to the formation of additional stars far from existing ones, is consistent with the findings of radiationmagnetohydrodynamic simulations (Commerçon, Hennebelle & Henning 2011;Myers et al 2013). These show that radiation rather than magnetic fields is more important in prevent fragmentation close to growing stars.…”
Section: Critical Massessupporting
confidence: 88%
See 1 more Smart Citation
“…Indeed, we note that the relative unimportance of magnetic fields as opposed to radiation in preventing fragmentation on small scales around stars, as opposed to the formation of additional stars far from existing ones, is consistent with the findings of radiationmagnetohydrodynamic simulations (Commerçon, Hennebelle & Henning 2011;Myers et al 2013). These show that radiation rather than magnetic fields is more important in prevent fragmentation close to growing stars.…”
Section: Critical Massessupporting
confidence: 88%
“…Hansen et al (2012) and Krumholz, Klein & McKee (2012) included outflows with radiation, but not magnetic fields. The only published studies reporting radiation-magnetohydrodynamic simulations of the formation of multiple stars are those of Price & Bate (2009), Peters et al (2011), and Myers et al (2013. Only the last of these both includes protostellar outflows and, most importantly, forms enough stars that one can obtain meaningful statistics from it, albeit only in the mass range near the IMF peak that is best sampled.…”
Section: Introductionmentioning
confidence: 99%
“…The misalignment is expected if the angular momenta of dense cores are generated through turbulent motions (e.g., Burkert & Bodenheimer 2000;Seifried et al 2012b;Myers et al 2013;Joos et al 2013). Plausible observational evidence for it was recently uncovered by Hull et al (2013) using CARMA, who found that the distribution of the angle between the magnetic field on the 10 3 AU-scale and the bipolar outflow axis (taken as a proxy for the rotation axis) is consistent with being random.…”
Section: Magnetic Field-rotation Misalignmentmentioning
confidence: 97%
“…They found that rotationally supported disks (RSDs) do not form out of uniform and non-uniform cores under strong magnetic fields unless the field is misaligned with respect to the rotation axis (Hennebelle & Ciardi 2009). Turbulence has also been shown to help with disk formation (Santos-Lima et al 2012;Seifried et al 2012;Myers et al 2013;Joos et al 2013;Li et al 2014b).…”
Section: Introductionmentioning
confidence: 99%